Cation–π interactions of methylated ammonium ions: A quantum mechanical study. Issue 7 (18th February 2014) - Rapp, Chaya; Goldberger, Elizabeth; Tishbi, Nasim; Kirshenbaum, Rachel
ABSTRACT Cation–π interactions of methylated ammonium ions play a key role in a broad range of biochemical systems. These include methyl‐lysine binding proteins which bind to methylated sites on histone proteins, lysine demethylase enzymes which demethylate these sites, and neurotransmitter receptor complexes which bind choline‐derived ligands. Recognition in these systems is achieved through an 'aromatic cage' motif in the binding site. Here we use high‐level quantum mechanical calculations to address how cation–π interactions of methylated ammonium ions are modulated by a change in methylation state and interaction geometry. We survey methyl‐lysine and choline‐derived complexes in the Protein Databank to validate our results against available structural data. A quantitative description of cation–π interactions of methylated ammonium systems is critical to structure‐based efforts to target methyl‐lysine binding proteins and demethylase enzymes in the treatment of unregulated transcriptional control, and neurotransmitter receptors in the treatment of neurological disease. It is our hope that our work will serve as a benchmark for the development of physical chemistry based force fields that can accurately model the contribution of cation–π interactions to binding and specificity in these systems. Proteins 2014; 82:1494–1502. © 2014 Wiley Periodicals, Inc.